Improving Marketability of Indian Business Education - Singh, R. P.; Yadav, Anil K. (Indian Journal of Marketing, 2004)
Business education all over the world is already in the process of speedy change in the present decade basically due to two reasons-accelerated dynamisity of the environment and better interaction of business education with other fields of education. The technology of manufacturing and marketing of goods and services, financial sector, advertising and research has undergone vast changes. The economic policies of the government have incorporated the elements of liberalization, privatization and globalization (LPG) of the corporate sector (though not necessarily of the peoples' economy). The market has become more consumer oriented with significant attention to demand assessment and demand creation. This has encouraged heavy (even cut-throat) competition, product diversification, innovation in product, process, presentation and service delivery, attention to quality and cost management. Currently, the business education is subject to significant developments in the global market and world communities. The globalization of markets is causing a transformation of the ways in which organizations compete and develop their business process. Â 